The Spatial Evolution of a European Hydrogen Economy - André Wolf (Intereconomics, 2023)
Green hydrogen has outgrown the testing stage: over the next few years, consortia across Europe will be investing large sums to build the supply chains of tomorrow. However, Europe as a whole will only be successful if it aligns the development of supply chains with the potentials of its regions and exploits the advantages of a European division of labour. This article examines the spatial distribution of hydrogen frontrunner projects in light of regional heterogeneity. It reveals a pattern that exhibits clear core regions but is only partly consistent with the localisation of current production and usage potentials. For a rapid ramp-up of hydrogen markets, European policymakers should make greater efforts to incentivise capacity formation in regions with high potential, by harmonising national levies affecting hydrogen supply chains and promoting the build-up of a cross-regional hydrogen transport infrastructure. Moreover, public investment support provided by various institutions and programmes should be better aligned to the common target of capacity upscaling.
Keywords: O14; Q42; R11; 330; renewable energy; hydrogen technology; Europe; Erneuerbare Energie; Wasserstofftechnik; Europa